1997
DOI: 10.1111/j.1432-2277.1997.tb00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Rescue therapy with tacrolimus in simultaneous pancreas/kidney transplantation

Abstract: Tacrolimus has been effective both in primary and rescue therapy following steroid and OKT3-resistant acute rejection in liver and kidney transplantation. Due to the effects of tacrolimus on glucose metabolism, there has been concern about its use in simultaneous pancreadkidney transplantation. We report on the results of six patients (three female, three male, age 35.2 k 7.3 years) converted from cyclosporin A to tacrolimus following simultaneous pancreadkidney transplantation in steroid-resistant acute rejec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…A large, multicenter, nonrandomized, case-matching analysis [91] showed FKbased immunosuppression to have a lower rate of rejection, particularly in solitary pancreas transplantation, which typically has a higher rate of rejection than simultaneous kidney-pancreas transplant. This multicenter study and other smaller studies [92,93] have demonstrated that FK can be used to treat rejection in place of steroids or ALA. Several of these studies have suggested that FK may have slightly more diabetogenicity than CsA in kidney-pancreas transplantation. No doubt this will be clarified as regimens are perfected and larger trials are done.…”
Section: Immunosuppression and Cancermentioning
confidence: 62%
“…A large, multicenter, nonrandomized, case-matching analysis [91] showed FKbased immunosuppression to have a lower rate of rejection, particularly in solitary pancreas transplantation, which typically has a higher rate of rejection than simultaneous kidney-pancreas transplant. This multicenter study and other smaller studies [92,93] have demonstrated that FK can be used to treat rejection in place of steroids or ALA. Several of these studies have suggested that FK may have slightly more diabetogenicity than CsA in kidney-pancreas transplantation. No doubt this will be clarified as regimens are perfected and larger trials are done.…”
Section: Immunosuppression and Cancermentioning
confidence: 62%
“…A large, multicenter, nonrandomized, case‐matching analysis [91] showed FK‐based immunosuppression to have a lower rate of rejection, particularly in solitary pancreas transplantation, which typically has a higher rate of rejection than simultaneous kidney–pancreas transplant. This multicenter study and other smaller studies [92,93] have demonstrated that FK can be used to treat rejection in place of steroids or ALA. Several of these studies have suggested that FK may have slightly more diabetogenicity than CsA in kidney–pancreas transplantation. No doubt this will be clarified as regimens are perfected and larger trials are done.…”
Section: Immunosuppression and Cancermentioning
confidence: 68%
“…So, this line of treatment is also endorsed [17]. It may, however, be mentioned that a switch to tacrolimus is also an option in the treatment of humoral and acute cellular rejection [18][19][20][21].…”
Section: Long-term Maintenance Immunosuppressive Medicationsmentioning
confidence: 99%